Traditional Chinese medicine for acute myelocytic leukemia therapy: exploiting epigenetic targets - Gao, Xinlong; Zuo, Xu; Min, Tianjiao; Wan, Yu; He, Ying; Jiang, Beier (Frontiers in Pharmacology, 2024)
Acute myeloid leukemia (AML) is a heterogeneous hematological malignancy with historically high mortality rates. The treatment strategies for AML is still internationally based on anthracyclines and cytarabine, which remained unchanged for decades. With the rapid advance on sequencing technology, molecular targets of leukemogenesis and disease progression related to epigenetics are constantly being discovered, which are important for the prognosis and treatment of AML. Traditional Chinese medicine (TCM) is characterized by novel pharmacological mechanisms, low toxicity and limited side effects. Several biologically active ingredients of TCM are effective against AML. This review focuses on bioactive compounds in TCM targeting epigenetic mechanisms to address the complexities and heterogeneity of AML.